Effects of topical azithromycin, moxifloxacin, and povidone iodine on conjunctival bacterial flora in patients undergoing intravitreal injection - Teberik,Kuddusi (2019)
ABSTRACT Purpose: To compare effects of 5% topical povidone iodine with prophylactic topical azithromycin and moxifloxacin on bacterial flora in patients undergoing intravitreal injection. Methods: A total of 132 patients were randomly assigned to receive treatment with azithromycin or moxifloxacin, or no treatment (control group). In total, 528 specimens were obtained at the time of admission, 4 days before intravitreal injection, 4 days after intravitreal injection, and 8 days after intravitreal injection. Samples were immediately sent to the microbiology laboratory for incubation. Results: The microorganism observed most frequently was coagulasenegative Staphylococcus (23.8%). When the results of samples obtained on Day 4 before injection were assessed, growth of coagulase-negative Staphylococcus was significantly lower in the moxifloxacin group, compared with controls (p=0.049). Acinetobacter baumannii continued to grow after administration of azithromycin (p=0.033). When the results of four days after intravitreal injection were evaluated, growth of coagulase-ne gative Staphylococcus was higher in controls, compared with patients who received azithromycin or moxifloxacin (p=0.004). Eradication rate was significantly higher in the moxifloxacin group than in the control group (p=0.001). Samples obtained on Day 8 after intravitreal injection showed similar levels of bacterial growth in all groups (p=0.217). Conclusion: Moxifloxacin was more effective than 5% povidone iodine in controlling the growth of conjunctival bacterial flora. Use of moxifloxacin in combination with 5% povidone iodine resulted in a synergistic effect.